POSTHUMOUS REPRODUCTION: LIFE AFTER DEATH? - Barać, Ivana (Pravni zapisi, 2023)
This paper reviews the issue of posthumous reproduction at the international and domestic levels. The overview covers the legal systems of the United Kingdom, as a country that allows posthumous reproduction, and France, as a country that prohibits posthumous reproduction. Subsequently, Serbian legal provisions, which forbid posthumous reproduction, are analyzed. The provisions are analyzed through the lens of the recent private initiative submitted to Serbian national authorities. Although infertility is a great obstacle in life, the proposed amendments present are one-sided as they mainly focus on fulfilling the individual’s wish to become a parent, rather than on creating a legal framework. As a result, and bearing in mind that no consensus has been reached regarding the issue of permissibility of posthumous reproduction, the author determines that Serbian legislator is not at fault – at least for the time being.
Keywords: medically assisted reproduction; posthumous reproduction; written consent; the right to respect for private and family life; the child’s right to know their origins